Hubungan Sikap, Sosial Budaya, Dan KIE (Komunikasi, Informasi, Edukasi) Terhadap Keikutsertaan Ibu Dalam Mengikuti Program KB IUD Di Wilayah Puskesmas Jatirahayu Bekasi Jawa Barat : Relationship of Attitude, Socio-Culture, and IEC (Communication, Information, Education) to Mothers' Participation in the IUD Family Planning Program in the Jatirahayu Health Center Area, Bekasi, West Java - Mukti, Tati Sri (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: An Intra-Uterine Device (IUD) is a long-term non-hormonal contraceptive that is inserted in the uterus and is made of a plastic/copper-like material and has various shapes. Participation in IUD KB is the behavior of women in following all procedures for using IUD contraception, such as the initial examination before installation, the installation procedure, and the examination after installation. This study aims to determine the relationship between attitude, socio-culture, and KIE on the participation of mothers in the IUD family planning program in the Jatirahayu Health Center area. Methods: Using descriptive analytics with a cross-sectional approach. The sampling technique used was total sampling with a total of 33 respondents. Results: The results showed that there was a relationship between attitudes towards participation in the IUD family planning program, which obtained a p-value of 0,039; but there was no relationship between socio-culture and participation in the IUD family planning program p-value of 0,425; and KIE towards participation in the IUD family planning program p-value 1,000. Discussion: This study concludes that there is a relationship between attitudes towards participation in the IUD family planning program and no relationship between socio-culture and KIE towards participation in the IUD family planning program for mothers in the working area of the Jatirahayu Health Center in 2023. Suggestions for prospective family planning acceptors are expected to increase knowledge of the benefits and effectiveness of IUD family planning to foster trust and motivation to participate in the IUD family planning program.